Characteristics and sources of PM2.5 with focus on two severe pollution events in a coastal city of Qingdao, China. (May 2020) - Gao, Yang; Shan, Huayao; Zhang, Shaoqing; Sheng, Lifang; Li, Jianping; Zhang, Junxi; Ma, Mingchen; Meng, He; Luo, Kun; Gao, Huiwang; Yao, Xiaohong
Abstract: In this study, the seasonal mean PM2.5 concentration in Qingdao, a coastal city, during 2014–2018 was first analyzed and the winter, in particular of 2015, showed the highest concentration. To elucidate the sources and control factors of PM2.5, three dimensional model Weather Research and Forecasting (WRF), Community Multiscale Air Quality model (CMAQ), as well as Flexible Particle model (FLEXPART), were used. During December 2015 and January 2016, modeling results showed that the mean contribution to PM2.5 mass concentrations from local emissions in Qingdao was 25%, and the transport from north and west accounted for almost half. Over the two episodically polluted periods (29–31 December 2015; 15–17 January 2016), the local emissions in Qingdao surprisingly contributed to only 18% and 24% to PM2.5 mass concentrations, respectively, indicating the dominant contributions from other regions, such as areas outside Qingdao in Shandong and Beijing-Tianjin-Hebei (BTH). The results show the sources region and contribution may vary remarkably along with the change in the pathways of the air parcel, inferred by the FLEXPART, while the near-surface PM2.5 enhancement is largely caused by downward vertical advection and enhanced aerosol chemistry reactions, accompanied by simultaneous drop in the boundary layer height. This study also reveals that the transport contribution is sensitive to the air parcel trajectories. We, therefore, recommend the efficient emission control based on transport trajectories in short-term air quality improvement in Qingdao. Highlights: The local emission in Qingdao only contributed on average of one fourth during winter 2015. The transport plays a major role in modulating the air pollution in Qingdao. The sources of PM2.5 in Qingdao may vary dramatically in a short period of time.